2006
DOI: 10.1002/hon.785
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of venous thromboembolism in cancer: emerging links with tumour biology

Abstract: Venous thromboembolism (VTE) is a frequent complication in individuals with cancer and is considered to be a cause of substantial mortality. Epidemiological studies identify malignancy as an independent VTE risk factor and show that cancer patients are at increased risk of both initial and recurrent VTE events. The risk due to cancer is compounded by the effects of chemotherapy and other treatments. The pathogenesis of cancer-associated VTE is complex involving multiple interactions between tumours and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 98 publications
(111 reference statements)
0
35
0
Order By: Relevance
“…Our study was conducted in serum; however, we still observed the ladder of peptides derived from fibrinogen α when we analyzed EDTA plasma from disease free controls. Cancer is known to be associated with disorders of hemostasis and it is still unclear how much fragmentation occurs in vivo and what are the functional implications [46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was conducted in serum; however, we still observed the ladder of peptides derived from fibrinogen α when we analyzed EDTA plasma from disease free controls. Cancer is known to be associated with disorders of hemostasis and it is still unclear how much fragmentation occurs in vivo and what are the functional implications [46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its frequent mention in reviews, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] the term Trousseau's syndrome is not in the MeSH headings of Medline or PubMed. Literature searching is confounded by the insistence of some journal editors on using "Trousseau syndrome."…”
Section: What Is Trousseau's Syndrome?mentioning
confidence: 99%
“…[30][31][32] Such findings suggested that activators of fluid-phase coagulation were the key to the pathogenesis. [9][10][11][12][13][14][15][16][17] This review concludes that Trousseau's syndrome is actually a spectrum of disorders and considers additional molecular mechanisms that have more recently pointed to pathways for its initiation. This is done recognizing how little we still understand about this syndrome, and yet how important it is to seek a better understanding of it.…”
Section: Early Theories About Mechanisms Of Trousseau's Syndromementioning
confidence: 99%
“…The association between malignancy and thrombosis has been reported in many studies [1,2] . Cancer cells activate the hemostatic system by producing molecules with procoagulant, fibrinolytic or proaggregating activities.…”
mentioning
confidence: 90%